Current practices in the management of malignant pleural effusions: a survey among members of the European Society of Thoracic Surgeons - BATIREL, HASAN FEVZİ (OXFORD UNIV PRESS, 2016)
OBJECTIVES: Malignant pleural effusion (MPE) commonly complicates advanced malignancy and their exact management is still undefined. We undertook a survey to determine the current practice among members of the European Society of Thoracic Surgeons (ESTS). METHODS: A cross-sectional survey focused on the current practice of management of MPE was developed by the authors. The questions were outlined after a review of the literature and circulated in an Internet-based survey format. RESULTS: Computed tomography (125, 92%) and chest X-ray (106, 78%) are the most common imaging modalities performed in the initial evaluation. Video-assisted thoracoscopic surgery for washout and pleurodesis (93, 68%) was reported as the preferred approach to patients with uncomplicated MPE. Sixty-one (45%) of the responding colleagues routinely use large bore chest tubes for draining malignant effusions. Forty-nine (35%) surgeons would not apply suction to the drainage system, whilst 50 (37%) would use -2 kPa or less. Talc (124, 91%) is the most commonly used sclerosing agent for pleurodesis in the context of malignant pleural effusion. The practice of 76 (56%) of the respondents is not informed by any clinical guidelines, whilst 60 (44%) reported adhering to the 2010 British Thoracic Society Pleural Disease Guideline. Seventy-one (52%) declared that the guidance was in need of updating or revision. CONCLUSIONS: This survey demonstrates the lacking adoption of the existing clinical guidance in this field, as well as the need for more contemporary guidelines for a better-informed practice. The ESTS Working Group on the management of MPE has been established for this purpose.
Keywords: Malignant pleural effusion; Survey; ESTS Malignant Pleural Effusion Working Group; QUALITY